Effect of Weather Parameters on Wheat Productivity: A Statistical Analysis Using SPSS - Negi, Ankita; Rana, Kuldeep; Singh, Shweta; Shahi, Uday Pratap (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted during the year March, 2021 to March, 2022 at Krishi Vigyan Kendra (KVK) Baghpat, Uttar Pradesh, India under Gramin Krishi Mausam Seva-District Agromet Unit (GKMS-DAMU) scheme to identify the effects of weather parameters on wheat productivity in two districts of Uttar Pradesh, namely Baghpat and Meerut for the five rabi seasons (October-April) from 2012 to 2017 using statistical analysis technique in the Statistical Package for the Social Sciences (SPSS). The study utilized in-situ collected weekly data of weather parameters viz., bright sunshine hours, maximum temperature, minimum temperature, rainfall, maximum relative humidity, minimum relative humidity and wind speed. The data of wheat yield (t ha-1) was collected from Directorate of Economics and Statistics, Department of Agriculture website (http://aps.dac.gov.in/APY/Public_Report1.aspx). The SPSS analysis revealed that weather conditions play a significant role in wheat productivity in both districts. The results showed that maximum temperature during April first week had a positive correlation with wheat yield for Baghpat district. Meanwhile, in Meerut, the most significant weather parameters that affected wheat yield were February’s fourth week rainfall, followed by bright sunshine hours of March third week, and minimum relative humidity of April third week. It was also observed that intense rainfall reduced wheat yield in Meerut during the 2014–15 Rabi season. The findings of present study could be useful for policymakers & farmers in developing strategies to improve wheat productivity. The study emphasized the importance of considering local weather conditions for better decision making in agricultural operations.